Epidemiology of mammary gland cancer in Uruguay - Valls, Alberto; Lerena, Ana; Ricciardi, Norma (Cirugía del Uruguay, 1984)
This paper showed the extraordinary importance of mammary gland cancer in Uruguay, the first in Amerir::a and sixth in the world in the frequency rate which continues to increase as a functlon of the low level in the birth rate.